Evaluation of clusters of credit cards holders - Martins, M. C.; Cardoso, M. G. M. S. (Revista de Ciências da Computação, 2008)
This work is focused on the evaluation of a clustering of credit card holders of a Portuguese financial organization, using a cross-validation procedure which is imported from supervised learning and used for evaluating results yielded by cluster analysis (an unsupervised technique). The proposed approach is conceived to deal with the particular sample characteristics – it handles a large data set and mixed (numerical and categorical) variables. This approach provides both the evaluation of the clustering solution and helps characterizing the clusters. Furthermore, it provides classification rules for new credit card holders. According to the obtained results, the internal stability is verified for a solution with five clusters. Finally, this work presents the profiles of the credit card holders’ clusters and suggests some possible strategies to study in each of them, in the business context.